Geographic range extension of the Waterscorpion Curicta scorpioStål, (Hemiptera: Nepidae) and first record for Costa Rica - Herrera, Federico (2013)
Curicta scorpioStål.c is registered for first time to Costa Rica. With this record this genus is confirmed in Costa Rica and its southern range distribution in turn is expanded.